State-Level Indicators of Structural Racism and Severe Adverse Maternal Outcomes During Childbirth. - Guglielminotti, Jean; Samari, Goleen; Friedman, Alexander M.; Landau, Ruth; Li, Guohua (Maternal & Child Health Journal, 2024)
Objectives: Structural racism (SR) is viewed as a root cause of racial and ethnic disparities in maternal health outcomes. However, evidence linking SR to increased odds of severe adverse maternal outcomes (SAMO) is scant. This study assessed the association between state-level indicators of SR and SAMO during childbirth. Methods: Data for non-Hispanic Black and non-Hispanic white women came from the US Natality file, 2017–2018. The exposures were state-level Black-to-white inequity ratios for lower education level, unemployment, and prison incarceration. The outcome was patient-level SAMO, including eclampsia, blood transfusion, hysterectomy, or intensive care unit admission. Adjusted odds ratios (aORs) of SAMO associated with each ratio were estimated using multilevel models adjusting for patient, hospital, and state characteristics. Results: A total of 4,804,488 birth certificates were analyzed, with 22.5% for Black women. SAMO incidence was 106.4 per 10,000 (95% CI 104.5, 108.4) for Black women, and 72.7 per 10,000 (95% CI 71.8, 73.6) for white women. Odds of SAMO increased 35% per 1-unit increase in the unemployment ratio for Black women (aOR 1.35; 95% CI 1.04, 1.73), and 16% for white women (aOR 1.16; 95% CI 1.01, 1.33). Odds of SAMO increased 6% per 1-unit increase in the incarceration ratio for Black women (aOR 1.06; 95% CI 1.03, 1.10), and 4% for white women (aOR 1.04; 95% CI 1.02, 1.06). No significant association was observed between SAMO and the lower education level ratio. Conclusions for Practice: State-level Black-to-white inequity ratios for unemployment and incarceration are associated with significantly increased odds of SAMO. Significance: What is already known on this subject? Structural racism is viewed as a root cause of racial and ethnic disparities in maternal health outcomes, independent of socioeconomic determinants of health. However, supporting evidence is scant. What this study adds? In this population-based study in 2017–2018, state-level Black-to-white inequities in unemployment and incarceration are associated with significantly increased odds of severe adverse maternal outcomes (i.e., blood transfusion, hysterectomy, and ICU admission) during childbirth for non-Hispanic Black women, and to a lesser extent, for non-Hispanic white women. Addressing structural racism in maternal care may contribute to improving maternal health equity.